2007
DOI: 10.3892/ijmm.20.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory status in patients with chronic renal failure: The role of PTX3 and pro-inflammatory cytokines

Abstract: Increased plasma levels of several acute phase proteins, such as C-reactive protein (CRP), have been documented among different patients with chronic renal failure (CRF). The aim of the present study was to determine whether pentraxin-3 (PTX3) is a reliable marker of inflammation in CRF. Plasma samples and monocytes were taken from 43 patients before and after undergoing haemodialysis (HD), from 45 uraemic patients (UR) without HD treatment and from 25 healthy controls. Plasma and monocyte samples were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 77 publications
4
24
0
Order By: Relevance
“…Other studies have shown that PTX-3 has a more stable course (16), relation between CRP and PTX-3 is weak (8,12), PTX-3 is related with IL-6 more strongly than CRP (15) and the relationship between IL-6 levels and cardiovascular disease risk is stronger (2). From our findings, together with these literature data, it may be said that PTX-3 is superior to CRP as an inflammation marker.…”
Section: Discussionsupporting
confidence: 73%
“…Other studies have shown that PTX-3 has a more stable course (16), relation between CRP and PTX-3 is weak (8,12), PTX-3 is related with IL-6 more strongly than CRP (15) and the relationship between IL-6 levels and cardiovascular disease risk is stronger (2). From our findings, together with these literature data, it may be said that PTX-3 is superior to CRP as an inflammation marker.…”
Section: Discussionsupporting
confidence: 73%
“…[15][16][17] In addition, PTX-3 may have a more stable course than CRP. 18 Cytokines, complement components, and fibrinolytic agents are released with the ischemia-reperfusion injury that occurs during transplant. 19 However, the effects of PTX-3 during this injury have not been studied sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al (6) found that the relation between IL-6 and PTX-3 was stronger than that between IL-6 and CRP. It has been shown by previous studies that PTX-3 has a more stable course (20). It was shown to be weakly correlated with CRP (13,21), while more closely related with IL-6 (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is regarded as an independent marker of disease activity due to its synthesis directly at the site of inflammation. Uremic patients have high PTX-3 levels, which are related with increased mortality independent of CRP (6,19); it has a more stable course than CRP (20). The relationship of PTX-3 with CRP has been reported to be weak in some studies (13,21).…”
Section: Introductionmentioning
confidence: 99%